Qurʼānic Christians: an analysis of classical and modern exegesis - McAuliffe, Jane Dammen (Cambridge University Press, 1991)
The Muslim perception of Christianity and Christians is an issue of longstanding debate among scholars of both Islam and Christianity. In this book, Jane McAuliffe analyses a series of passages from the Qur'an that make ostensibly positive remarks about Christians. She conducts this analysis through a close examination of Muslim exegesis of the Qur'an, spanning ten centuries of commentary. In this effort to trace various interpretations of these passages, the author attempts to determine whether these positive passages can justifiably serve as proof-texts of Muslim tolerance of Christianity. She finds that commentators have consistently distinguished between the vast majority of Christians, who are denounced for having turned from the true word of God, and a small minority, who accepted the prophethood of Muhammed and are praised.